2018
DOI: 10.1155/2018/9207678
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Transplantation of Mesenchymal Stem Cells Reduces the Number of Infiltrated Ly6C+ Cells but Enhances the Proportions Positive for BDNF, TNF-1α, and IL-1β in the Infarct Cortices of dMCAO Rats

Abstract: The resident microglial and infiltrating cells from peripheral circulation are involved in the pathological processes of ischemia stroke and may be regulated by mesenchymal stem/stromal cell (MSC) transplantation. The present study is aimed at differentiating the neurotrophic and inflammatory roles played by microglial vs. infiltrating circulation-derived cells in the acute phase in rat ischemic brains and explore the influences of intravenously infused allogeneic MSCs. The ischemic brain injury was induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…For these reasons, MSCs are the first stem cells to have been tested in clinical studies for the treatment of stroke. Preclinical studies demonstrated that administration of MSCs via intracerebral (10,11), intravenous (12)(13)(14), intra-arterial (15,16), and intraventricular/intrathecal routes (17) showed therapeutic benefits of MSCs in animal models of acute stroke (18). Although intravenous administration of autologous MSCs from bone marrow was found to be safe and well tolerated in ischemic stroke patients (19)(20)(21)(22), no significant improvement was observed in neurological outcomes following intravenous administration of allogeneic MSCs (23).…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, MSCs are the first stem cells to have been tested in clinical studies for the treatment of stroke. Preclinical studies demonstrated that administration of MSCs via intracerebral (10,11), intravenous (12)(13)(14), intra-arterial (15,16), and intraventricular/intrathecal routes (17) showed therapeutic benefits of MSCs in animal models of acute stroke (18). Although intravenous administration of autologous MSCs from bone marrow was found to be safe and well tolerated in ischemic stroke patients (19)(20)(21)(22), no significant improvement was observed in neurological outcomes following intravenous administration of allogeneic MSCs (23).…”
Section: Introductionmentioning
confidence: 99%
“…The activated microglia stain positive for CD68 ( Figure 1 ), and both activated and resting stage microglia are positive for Iba-1. In our previous studies, we reported that CD68+ microglia express IGF-1 in the brain of a stroke model [ 15 , 19 ]. In the present study, we continued to look into a wider range of microglia population—Iba-1+ cells, with regard to IGF-1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of allogeneic bone marrow MSC (BMSC) culture, infusion, dMCAO model establishment, and behavioral tests have been described in our previous study [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations